Trust in central banks - Michael Ehrmann (European Central Bank (ECB), 2024)
Trust in the central bank is an essential ingredient for a successful conduct of monetary policy. However, for many central banks trust has recently declined, for instance in the wake of the post-pandemic inflation surge, due to large errors in central banks' inflation forecasts, or given problems when exiting from forward guidance. The rapid, substantial and persistent erosion of trust makes it clear that trust needs to be earned continuously. This paper reviews why trust is important, what determines it and how central banks can enhance it. It also argues that it is important for central banks to improve the measurement and monitoring of trust. It ends by highlighting some future challenges for maintaining trust.
Keywords: E52; E58; G53; 330; trust; credibility; central banks; monetary policy; inflation expectations